Transcriptome and co-expression network analysis reveal the genetic basis of cell wall components in maize stalks - Yao He; Zhike Deng; Shijiang He; Zhaojie Qi; Hengshuo Chang; Peng Liu; Zhong Chen; Chaoying Zou; Yaou Shen; Langlang Ma (BMC Genomics)
Abstract Cellulose (CEL), hemicellulose (HCE), and lignin (LIG) are crucial constituents of the cell wall in maize stalks, significantly influencing stalk resistance to lodging and external stresses. The proportion of these contents also determines the application of maize stalks in animal feed, energy production, and other fields. Herein, two maize inbred lines with contrasting cell wall component contents in the stalk, MO190 (high CEL, HCE, and LIG contents) and MO194 (low CEL, HCE, and LIG contents), were subjected to analysis of transcriptomes at the seedling, jointing, silking, and grain stages. By comparing the differentially expressed genes (DEGs) during stalk development between the two lines, 11,546 genes were identified as the specific DEGs in each line. Using traits-associated WGCNA (weight gene co-expression network analysis), we identified a hub co-expression module and 26 key genes regulating the CEL, HCE, and LIG contents in the stalk. Based on the eigengene-based connectivity value in the module, the four genes Zm00001d019317, Zm00001d027313, Zm00001d043965, and Zm00001d019149 were confirmed as the hub genes affecting these contents. Among these, Zm00001d019317 that encodes CEL synthase-8 was significantly associated with CEL content in the stalk via gene-based association studies. Maize lines carrying the “deletion” allele in the promoter region of Zm00001d019317 exhibited significantly higher CEL content compared to those with the “C” allele. Our study helps to understand the variation mechanism of cell wall component contents in maize stalks and contributes to genetic modification of maize resistance to stalk lodging.